1988
DOI: 10.1128/mcb.8.12.5100
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of the human chorionic gonadotropin beta subunit (CG beta) gene cluster: regulation of transcriptionally active CG beta gene by cyclic AMP.

Abstract: The a and I subunit genes encoding chorionic gonadotropin (CG) are regulated transcriptionally in placental cells by cyclic AMP (cAMP). The regulatory response sequences of the a gene have been studied extensively. Similar studies of the CG j8 subunit (CGI) gene have not been possible because transcriptionally active sequences have not been identified in the clones isolated to date. The CGi subunit genes form a complex cluster of seven structurally similar genes that include six CG,(-like genes and a single lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…SB). To test this, (7,29,30,40). Temporal regulation of the human P450scc promoter by cAMP was even more rapid than that of the hCGa CRE (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…SB). To test this, (7,29,30,40). Temporal regulation of the human P450scc promoter by cAMP was even more rapid than that of the hCGa CRE (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The promoter activity of hCG␤5 was stimulated by 8-bromo-cAMP in human JEG-3 placental cells but not hamster BHK fibroblast or INR1-G9 islet cells (26). It was later reported that the activating protein 2 (AP2) transcription factors TFAP2A and TFAP2C bind to GC-rich DNA sequences in the cAMP-responsive region the of hCG␤5 promoter (27)(28)(29)(30).…”
mentioning
confidence: 99%
“…5). This proposed genesis and structure of white rhino LH loci contrasts with the primate LH -CG gene cluster-locus wherein the repeated members of the gene family are tandemly linked (Talmadge et al 1983, Policastro et al 1983, Graham et al 1987, Jameson & Lindell 1988, having evolved by a different replicative process involving unequal crossing over of adjacent DNA regions (Stark & Wahl 1995).…”
Section: Discussionmentioning
confidence: 99%